Komunikasi Lingkungan bagi Tumbuh Kembang Anak melalui Literasi Digital - Wiyati, Eni Kardi; Widarini, Dwi Ajeng; Sukmarini, Herlin (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The environment plays a crucial role in child growth and development and can contribute to stunting. Poor environmental sanitation, exposure to pollution, and limited access to clean water can increase the risk of stunting. Stunting, which disrupts linear growth in children, can have long-term impacts on their health, cognitive development, and quality of life. By improving the environment and implementing good health practices, communities can help children grow and develop optimally and prevent stunting. The objective of this activity is to educate the community through digital literacy to foster child development. The activity methods include outreach, digital literacy training, website usage training, and mentoring and monitoring. The activity was carried out in the Sukaresmi Village Community Group, funded by the Directorate General of Research and Development, Ministry of Higher Education, Science, and Technology. The activity resulted in the implementation of outreach and information dissemination on the overall activity. In addition, training on digital literacy and the implementation of the pokmassukaresmi.com website were also conducted. The Community Service Program (PKM) activities increased community knowledge about the use of digital literacy as access to information on environmental health in preventing stunting. Furthermore, through the Pokmas website, the Pokmas' performance in strengthening Pokmas institutions was improved.